2007
DOI: 10.1128/jvi.02311-06
|View full text |Cite
|
Sign up to set email alerts
|

Caspase 3-Dependent Cell Death of Neurons Contributes to the Pathogenesis of West Nile Virus Encephalitis

Abstract: West Nile virus (WNV) is a neurotropic, arthropod-borne flavivirus that has become a significant global cause of viral encephalitis. To examine the mechanisms of WNV-induced neuronal death and the importance of apoptosis in pathogenesis, we evaluated the role of a key apoptotic regulator, caspase 3. WNV infection induced caspase 3 activation and apoptosis in the brains of wild-type mice. Notably, congenic caspase 3 ؊/؊ mice were more resistant to lethal WNV infection, although there were no significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
177
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 162 publications
(186 citation statements)
references
References 65 publications
9
177
0
Order By: Relevance
“…Indeed, the nonneuropathogenic phenotype of some strains of WNV has been attributed to an inability to invade the CNS (12,13,27). Increasing evidence suggests that WNV entry into the CNS is a multistep process that can occur through one of several routes (17,20,(31)(32)(33)(34)(35). WNV entry into the CNS has been shown to precede disruption of the BBB and leukocyte infiltration (32,33,36,37), suggesting that WNV utilizes a direct mechanism to initially invade the CNS, such as basolateral secretion of virus particles from infected brain endothelial cells or transcytosis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the nonneuropathogenic phenotype of some strains of WNV has been attributed to an inability to invade the CNS (12,13,27). Increasing evidence suggests that WNV entry into the CNS is a multistep process that can occur through one of several routes (17,20,(31)(32)(33)(34)(35). WNV entry into the CNS has been shown to precede disruption of the BBB and leukocyte infiltration (32,33,36,37), suggesting that WNV utilizes a direct mechanism to initially invade the CNS, such as basolateral secretion of virus particles from infected brain endothelial cells or transcytosis.…”
Section: Discussionmentioning
confidence: 99%
“…reduced neuronal death compared with wild-type mice, despite having comparable viral loads in their brain [183]. Similarly, inhibition of caspase activity reduced WNVmediated neuronal death in primary neuronal culture [183].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 99%
“…Neuronal damage and loss can occur by either direct arboviral infection or indirectly by uncontrolled immune responses to the replicating virus [181,182]. In vitro and in vivo studies have shown that neurons undergo morphologic changes that are characteristic of apoptosis, that is, nuclear and membrane condensation, after infection with several encephalitic flaviviruses, including WNV [183], JEV [154], TBEV [184], and alphaviruses [145,185,186]. Neuronal degeneration, necrosis, and apoptosis were also demonstrated in various CNS regions in mice infected with LACV [146].…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 99%
“…Although most WNV infections are asymptomatic or manifest as a mild, flu-like illness, potentially fatal neuroinvasive infections occur in the elderly or those who are immunocompromised, including meningitis, encephalitis, and anterior myelitis. In the CNS, WNV targets cortical, midbrain, cerebellar, and spinal cord neurons leading to their injury or death (31)(32)(33)(34). The high incidence of WNV neuroinvasive disease in patients on anti-T cell therapies (35,36) and in mice with T cell deficiencies (37)(38)(39)(40) indicate that, similar to other neurotropic viruses, the clearance of WNV within the CNS relies heavily on cell-mediated immune responses that promote the migration and effector functions of T cells into the CNS parenchyma.…”
Section: T He Infiltration Of Virus-specific Cd8 T Cells Is Essentialmentioning
confidence: 99%